2007
DOI: 10.1038/sj.cgt.7701040
|View full text |Cite
|
Sign up to set email alerts
|

T-regulatory cells are relatively deficient in squamous carcinomas undergoing regression in mice immunized with a squamous carcinoma vaccine enriched for immunotherapeutic cells

Abstract: In a prior report (Int J Cancer 2006; 119: 339-348), we described a new vaccination strategy for squamous cell carcinoma (SCC). The vaccine was prepared by transfer of unfractionated DNA-fragments (25 kb) from KLN205 cells, a squamous carcinoma cell line (DBA/2 origin; H-2 d ) into LM cells, a highly immunogenic mouse fibroblast cell line (C3H/He origin; (H-2 k )). As only a small proportion of the transfected cell population was expected to have incorporated DNA segments that included genes specifying antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The KLN 205 cell line has been applied in around 100 published research studies. While morphologically it seems non-negotiable that KLN 205 in culture appears similar to SCC cells [12][13][14]24,25] , they have been applied as models for lung cancer in general [15][16][17][18][19][20][21][22] , metastatic lung cancer cells [26] and even non-small cell lung cancer [23] . Surprisingly, they have even worked as a model for tongue cancer [27] and subcutaneous SCC [28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The KLN 205 cell line has been applied in around 100 published research studies. While morphologically it seems non-negotiable that KLN 205 in culture appears similar to SCC cells [12][13][14]24,25] , they have been applied as models for lung cancer in general [15][16][17][18][19][20][21][22] , metastatic lung cancer cells [26] and even non-small cell lung cancer [23] . Surprisingly, they have even worked as a model for tongue cancer [27] and subcutaneous SCC [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that the patterns of gains and losses in human lung cancer (SCC-type) and human small cell lung cancer type are strikingly similar as well [31] . Thus, their use as models for SCC cells in general [12][13][14]24,25] or even for subcutaneous SCC [28] seems to be justifiable. In addition, considering their genetic background, KLN 205 can use as a model for lung cancer in general [15][16][17][18][19][20][21][22] , as as well as for even non-small cell lung cancer [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell mediated anti tumor immunity appears to be specific and mainly driven by CD8 T-cells. Regulatory T-cells are down-regulated by DNA-based vaccines as indicated by the reduction in the relative numbers of cells that express CD4/CD25, CD62L and Fox P3 [10,12] in the regressing tumors.…”
Section: Introductionmentioning
confidence: 99%